Integrated omics analyses of retrograde signaling mutant delineate interrelated stress‐response strata. (29th April 2017) - Bjornson, Marta; Balcke, Gerd Ulrich; Xiao, Yanmei; de Souza, Amancio; Wang, Jin‐Zheng; Zhabinskaya, Dina; Tagkopoulos, Ilias; Tissier, Alain; Dehesh, Katayoon
Summary: To maintain homeostasis in the face of intrinsic and extrinsic insults, cells have evolved elaborate quality control networks to resolve damage at multiple levels. Interorganellar communication is a key requirement for this maintenance, however the underlying mechanisms of this communication have remained an enigma. Here we integrate the outcome of transcriptomic, proteomic, and metabolomics analyses of genotypes including ceh1, a mutant with constitutively elevated levels of both the stress‐specific plastidial retrograde signaling metabolite m ethyl ‐erythritol c yclodi p hosphate (MEcPP) and the defense hormone s alicylic a cid (SA), as well as the high MEcPP but SA deficient genotype ceh1 / eds16, along with corresponding controls. Integration of multi‐omic analyses enabled us to delineate the function of MEcPP from SA, and expose the compartmentalized role of this retrograde signaling metabolite in induction of distinct but interdependent signaling cascades instrumental in adaptive responses. Specifically, here we identify strata of MEcPP‐sensitive stress‐response cascades, among which we focus on selected pathways including organelle‐specific regulation of jasmonate biosynthesis; simultaneous induction of synthesis and breakdown of SA; and MEcPP‐mediated alteration of cellular redox status in particular glutathione redox balance. Collectively, these integrated multi‐omic analyses provided a vehicle to gain an in‐depth knowledge of genome‐metabolism interactions, and to further probe the extent of these interactions and delineate their functional contributions. Through this approach we were able to pinpoint stress‐mediated transcriptional and metabolic signatures and identify the downstream processes modulated by the independent or overlapping functions of MEcPP and SA in adaptive responses. Significance Statement: The integrity of intra‐cellular communication networks regulated by retrograde signaling pathways is key in sustaining cellular homoeostasis in the dynamically changing environment. Utilization of integrated multi‐omic analyses allowed functional differentiation of SA from the plastidial retrograde signal, MEcPP, provided insight into genome‐metabolism interactions under stress and the resulting transcriptional and metabolic signatures, and finally identified causative downstream processes, revealing compartmentalized contribution of MEcPP to interorganellar stress network.